The value co-creation mechanism of Public Cultural Services ecosystem in China based on "public value" theory. - Xianke Li; Johnny Fat Iam Lam; Zhicong Lin; Ke Song (PLoS ONE)
The establishment of China's public cultural service system has been explored for nearly two decades, but there is still a significant gap in achieving the goal of equalising and eliminating differences in public value, and it is urgent to systematically explore the public value governance issues contained in it. This paper presents a localised theoretical analysis framework based on the strategic triangle model of public value, with the objective of exploring the endogenous mechanism of China's public cultural services ecosystem (PCSE). Furthermore, it constructs a panel vector autoregression (PVAR) model from a dynamic endogenous perspective, employing the STATA 16.0 software package to conduct empirical tests. The empirical testing of the interactions between government attention (GA), cultural needs (CN) and public cultural services (PCS), as well as the regional heterogeneity, is based on data from 31 provinces and municipalities in mainland China for the period of 2008-2022. The findings are as follows: (1) The unified analysis framework reveals a significant positive mutual promotion relationship between GA and PCS. In contrast, the two-way promotion relationship between CN and PCS is weak, while the relationship between GA and PCS is unstable. (2) The results of the dynamic response analysis demonstrate significant regional disparities in the value co-creation path of public cultural services. The circular transfer of CN and PCS is more pronounced in the eastern region, while the central-western regions rely more on the circular transfer of GA and PCS. This study offers insights for central and local governments to reinforce the value co-creation foundation of a service-oriented government, explore a value co-creation pathway tailored to local conditions, and construct a contemporary public cultural services ecosystem guided by the value of common prosperity in spiritual life.